The Interdisciplinary Stem Cell Institute’s Use of Food and Drug Administration-Expanded Access Guidelines to Provide Experimental Cell Therapy to Patients With Rare Serious Diseases - Khan, Aisha; Bellio, Michael A.; Schulman, Ivonne H.; Levi, Allan D.; Longsomboon, Bangon; Brooks, Adriana; Valasaki, Krystalenia; DiFede, Darcy L.; Pujol, Marietsy V.; Yavagal, Dileep R.; Bates, Karen E.; Si, Ming-Sing; et al. (Frontiers in Cell and Developmental Biology, 2021)
The United States Food and Drug Administration (FDA) provides guidance for expanded access to experimental therapies, which in turn plays an important role in the 21st Century Cures Act mandate to advance cell-based therapy. In cases of incurable diseases where there is a lack of alternative treatment options, many patients seek access to cell-based therapies for the possibility of treatment responses demonstrated in clinical trials. Here we describe the use of FDA’s expanded access Investigational New Drug (INDs) to address rare and emergency conditions that include: stiff person syndrome, spinal cord injury, traumatic brain stem injury, complex congenital heart disease, ischemic stroke, and peripheral nerve injury. We have administered both allogeneic bone marrow-derived mesenchymal stem cells (MSCs) and autologous Schwann Cells (SCs) therapy to patients upon emergency request using Single Patient Expanded Access (SPEA) INDs approved by the FDA. In this report, we present our experience with ten completed SPEA protocols.